Cool-feeling anion fabric and preparation method thereof
By combining negative ion fibers and cooling fibers in the fabric, and specific organizational processing, the existing fabrics cannot take into account the problem of cooling and negative ion performance, and realize the cooling, anti -fatigue and washing resistance of the fabric.
Patent Information
- Application Number
- CN202411536932.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing fabrics that can generate negative ions cannot take into account the cooling performance.
By wearing negative ion fiber and cellulose fiber blended to obtain the inner layers and cooling fiber and cellulose fiber blending to obtain outer fabrics, and the plasma treatment and microcapsule are compiled. Cooling and negative ion fabric.
The cooling performance of the fabric and the improvement of fatigue effects, while maintaining a good feel, breathability, and washing resistance.
Smart Images

Figure BDA0005111785450000121
Abstract
Description
Technical Field
[0001] The invention relates to the fields of textile, textile chemistry and dyeing and finishing engineering, and in particular to a cool negative ion fabric and a preparation method thereof. Background Art
[0002] In recent years, the improvement of environmental awareness and the pursuit of healthy life have made people have higher and higher requirements for clothing fabrics. Not only do they require them to be able to cover the body and keep warm, but they also have new requirements for soothing, deodorizing, absorbing harmful gases, antibacterial, reducing fatigue, comfort, breathability, moisture absorption and perspiration, antibacterial, etc. At the same time, they also want the fabrics to have certain health effects.
[0003] Negative ions help purify the air, boost immunity, improve sleep, relieve stress, improve mental state and resist oxidation. Negative ion textiles are made by adding natural mineral additives (such as tourmaline) during the fiber or dyeing process. The additives are polar crystal structures that generate negative ions during thermal motion. Studies have shown that the concentration of negative ions exceeds 1000 / cm 3 It helps human health and improves immunity.
[0004] At the same time, for spring and summer, when consumers choose spring and summer fabrics, they will take into account its durability, easy care and the need to meet consumers' daily activities. It is very important to choose the right fabric. Cotton, polyester and polyester-cotton fabrics are commonly used in spring and summer clothing. Among them, polyester-cotton combines the durability of polyester and the comfort of cotton. It is crisp, quick-drying, wear-resistant, elastic, easy to care for, and has a wide range of applications. However, due to the high temperature in summer, whether the fabric has a cool feeling has become an important factor for some consumers to judge whether to buy.
[0005] Cool feeling mainly refers to "cool feeling at the moment of contact", that is, the cool feeling felt by the skin due to the rapid transfer of heat when it comes into contact with fabrics that are lower than its temperature. Cool feeling fibers can be prepared using natural fibers and regenerated cellulose fibers that have a cooling effect, or using fibers added with mica powder and jade powder as raw materials to prepare cool feeling textiles. Another type of cool feeling fiber can be achieved by designing the fiber cross section. The special-shaped fiber cross section gives the fiber a longitudinal multi-groove structure, and these grooves are conducive to improving the wicking function. The optional cool feeling fibers include cool polyethylene fiber, jade fiber, nylon, modal fiber, Coolmax fiber (DuPont), SORONA fiber (DuPont), Supercool fiber (Shanghai Guida Technology Co., Ltd.) and CoolDry fiber (Quanzhou Haitian Textile Group).
[0006] In summary, a fabric that combines health benefits such as improving immunity and improving sleep with a cool feeling may be popular with consumers. Summary of the invention
[0007] The purpose of the present invention is to provide a cool negative ion fabric and a preparation method thereof, so as to overcome the problem that the existing fabrics capable of generating negative ions cannot provide a cool feeling.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a method for preparing a cool anion fabric, comprising:
[0010] The negative ion fiber is blended and interwoven with the cellulose fiber to obtain an inner layer fabric, the cool feeling fiber is blended and interwoven with the cellulose fiber to obtain an outer layer fabric, and the inner layer fabric and the outer layer fabric are interwoven and interwoven to obtain a fabric to be finished;
[0011] The inner layer of the fabric to be finished is sequentially subjected to plasma treatment and cooling microcapsule finishing; the outer layer of the fabric to be finished is sequentially subjected to plasma treatment and negative ion finishing to obtain the cooling negative ion fabric.
[0012] In an optional embodiment, at least one of the following features is met:
[0013] a. The mass fraction of negative ion fibers in the inner layer fabric is 70%-90%;
[0014] b. The mass fraction of cool fibers in the outer fabric is 70%-90%;
[0015] c. The mass fraction of the inner layer of the fabric to be finished is 40%-60%;
[0016] d. Cellulose fiber is selected from at least one of cotton fiber, modal, lyocell and viscose fiber;
[0017] e. Cooling fibers are selected from at least one of nylon, polyethylene nylon fiber and jade fiber;
[0018] f. Anion fiber is selected from at least one of bamboo charcoal fiber, germanium alloy fiber and rice husk carbon fiber;
[0019] g. The weave structure of the fabric to be finished is selected from one of double-sided fabric, pique weave and rib weave.
[0020] In an optional embodiment, the plasma treatment step includes: using a plasma cleaning machine to perform plasma treatment on the inner layer and the outer layer of the fabric to be finished, with a maximum radio frequency power of 17-19W and a treatment time of 6-10min;
[0021] And / or, the cooling microcapsule finishing comprises: firstly finishing the inner layer of the fabric to be finished with a first cross-linking agent, and then finishing the inner layer of the fabric to be finished with a composite microcapsule.
[0022] In an optional embodiment, the first cross-linking agent is selected from at least one of an organosilicon cross-linking agent, a polycarboxylic acid cross-linking agent and a polyacrylate cross-linking agent;
[0023] And / or, using the first crosslinking agent to finish the inner layer of the fabric to be finished after the plasma treatment includes: spraying 5-10g / L of the first crosslinking agent solution to the inner layer of the fabric to be finished, and then drying at 110-130°C for 5-7min, wherein the spraying amount is 70g / m 3 -120g / m 3 .
[0024] In an optional embodiment, the use of compound microcapsules to finish the inner layer of the fabric to be finished includes: first using a screen printing process to perform single-sided hydrophobic finishing, with a hydrophobic finishing area of 30-50%, and coating the slurry containing the compound microcapsule solution on the inner surface of the fabric to be finished by scraping, pre-baking the fabric at 100-120°C for 1-3 minutes, then baking at 130-160°C for 1-3 minutes, and then soaping, drying, and ironing to complete the inner layer finishing.
[0025] In an optional embodiment, the slurry includes a cool finishing agent COOL and a cool finishing agent T802.
[0026] In an optional embodiment, the slurry includes: 8-20 g / L of cool finishing agent COOL and 8-20 g / L of cool finishing agent T802, 20-30 wt % of hydrophobic finishing agent, 0.1-1 g / L of second cross-linking agent, 0.04-0.15% of aqueous thickener and the balance of water.
[0027] In an optional embodiment, the aqueous thickener is selected from aqueous polyurethane thickeners and natural organic polymer thickeners;
[0028] And / or, the hydrophobic finishing agent is selected from silicone hydrophobic agents;
[0029] And / or, the second cross-linking agent is selected from at least one of etherified hydroxymethyl melamine, ethylene oxide-based compounds, citric acid and polycarboxylic acids.
[0030] In an optional embodiment, the negative ion finishing includes: covering the outer layer of the fabric to be finished with a negative ion foam composite material, then pre-baking at a temperature of 60-80°C for 2-4 minutes, and baking at a temperature of 120-140°C for 1-3 minutes to complete the outer layer finishing.
[0031] And / or, the negative ion foam composite material comprises 28-56 g / L of tourmaline negative ion finishing liquid, 12-24 g / L of nano inorganic metal compound negative ion finishing liquid, 2-4 g / L of foaming agent and 1-2 g / L of foam stabilizer.
[0032] And / or, the raw materials of the negative ion foam composite material are mixed and stirred at a shear rate of 500-2000 r / min for 3-5 min to obtain the negative ion foam composite material.
[0033] In a second aspect, the present invention provides a cool anion fabric, which is prepared by the preparation method of the cool anion fabric described in any one of the aforementioned embodiments.
[0034] The present invention has the following beneficial effects:
[0035] The cool negative ion fabric prepared by the method of the embodiment of the present application can effectively improve the cooling performance and anti-fatigue effect of the fabric, while making the fabric have a good hand feel and air permeability, and the finished fabric has good wash resistance. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] The present application provides a method for preparing a cool negative ion fabric, comprising:
[0038] The negative ion fiber is blended and interwoven with the cellulose fiber to obtain an inner layer fabric, the cool feeling fiber is blended and interwoven with the cellulose fiber to obtain an outer layer fabric, and the inner layer fabric and the outer layer fabric are interwoven and interwoven to obtain a fabric to be finished;
[0039] The inner layer of the fabric to be finished is sequentially subjected to plasma treatment and cooling microcapsule finishing; the outer layer of the fabric to be finished is sequentially subjected to plasma treatment and negative ion finishing to obtain the cooling negative ion fabric.
[0040] The preparation method of the cool anion fabric of the present invention adopts a tissue design with different inner and outer fiber components, so that the fabric has a cool feeling and anti-fatigue performance, and the presence of cellulose fiber makes the fabric feel better. The cool fiber and cellulose fiber are blended as the inner layer fiber, and the inner layer tissue structure of the fabric is a relatively flat structure. Since the functionality of the cool feeling is related to the flatness of the fabric, the flatter the fabric, the better the contact cool feeling performance, so that the fabric close to the skin surface has a cool feeling function and a skin-friendly and comfortable touch, reducing the discomfort caused by rapid heat conduction; the anion fiber and cellulose fiber are blended as the outer layer fiber, which is conducive to increasing the amount of negative ion release and helps to relieve fatigue.
[0041] Plasma treatment can increase the active sites on the fabric surface, allowing the finishing agent used to better combine with it, thereby improving the height, coolness and anti-fatigue effects.
[0042] The cool negative ion fabric prepared by the method of the embodiment of the present application can effectively improve the cooling performance and anti-fatigue effect of the fabric, while making the fabric have a good hand feel and air permeability, and the finished fabric has good wash resistance.
[0043] In an optional embodiment, the preparation method of the cool negative ion fabric meets at least one of the following characteristics:
[0044] a. The mass fraction of negative ion fibers in the inner layer fabric is 70%-90%;
[0045] b. The mass fraction of cool fibers in the outer fabric is 70%-90%;
[0046] c. The mass fraction of the inner layer of the fabric to be finished is 40%-60%;
[0047] d. Cellulose fiber is selected from at least one of cotton fiber, modal, lyocell and viscose fiber;
[0048] e. Cooling fibers are selected from at least one of nylon, polyethylene nylon fiber and jade fiber;
[0049] f. Anion fiber is selected from at least one of bamboo charcoal fiber, germanium alloy fiber and rice husk carbon fiber;
[0050] g. The structure of the fabric to be finished is selected from one of double-sided fabric, pique fabric and rib fabric. The knitted fabric selects a double-sided fabric structure. The pique fabric and rib fabric structures have good air permeability, fast moisture absorption and perspiration, excellent comfort, and beautiful visual effects. They are widely used in clothing such as T-shirts and Polo shirts.
[0051] In an optional embodiment, the plasma treatment step includes: using a plasma cleaning machine to perform plasma treatment on the inner layer and the outer layer of the fabric to be finished, with a maximum radio frequency power of 17-19W and a treatment time of 6-10 minutes.
[0052] In some implementations, a Harrick basic plasma cleaning machine PDC-32G-2 is used to treat the blended fabric for 6-10 minutes at a maximum radio frequency power of 18W, so that free radicals are attached to the fabric, which can effectively improve the bonding strength between the functional finishing agent and the fabric during subsequent functional finishing.
[0053] Plasma treatment can change the morphology of the fiber surface, introduce free radicals, and promote the cross-linking reaction between the material and the finishing agent, thereby improving the performance of the fabric.
[0054] In some embodiments, the cooling microcapsule finishing comprises: first finishing the inner layer of the fabric to be finished with a first cross-linking agent, and then finishing the inner layer of the fabric to be finished with a composite microcapsule;
[0055] In an optional embodiment, the first cross-linking agent is selected from at least one of an organosilicon cross-linking agent, a polycarboxylic acid cross-linking agent and a polyacrylate cross-linking agent;
[0056] In an optional embodiment, the first crosslinking agent is used to finish the inner layer of the fabric to be finished after the plasma treatment, including: spraying 5-10g / L of the first crosslinking agent solution to the inner layer of the fabric to be finished, and then drying at 110-130°C for 5-7min, wherein the spraying amount is 70g / m 3 -120g / m 3 .
[0057] In an optional embodiment, the use of compound microcapsules to finish the inner layer of the fabric to be finished includes: first using a screen printing process to perform single-sided hydrophobic finishing, with a hydrophobic finishing area of 30-50%, and coating the slurry containing the compound microcapsules on the inner surface of the fabric to be finished by scraping, pre-baking the fabric at 100-120°C for 1-3 minutes, then baking at 130-160°C for 1-3 minutes, and then soaping, drying, and ironing to complete the inner layer finishing.
[0058] The fabric is treated with a cross-linking agent by spraying, and then treated with a cool compound microcapsule. This finishing method can enhance the strength and stability of the microcapsule wall, control the release of the core material, improve durability and thermal stability, improve compatibility with the substrate, make the microcapsule more firmly bonded to the fabric surface, and produce better effects within a limited area, thereby improving the cooling performance and giving the fabric a good feel.
[0059] By using a screen printing process and a screen with a preset shape and mesh coverage, a single-sided hydrophobic finishing method can reserve a portion of the perspiration channel. This method can not only produce a differential capillary effect on both sides of the fabric, but also reserve a channel for the timely discharge of sweat. The reduction in finishing area means an increase in the difficulty of permeability, and the corresponding amount of thickener used will be reduced, and the fabric feel will be closer to unfinished fabric. In some embodiments, the area of hydrophobic finishing is adjusted by adjusting the size of the area occupied by the mesh in the screen.
[0060] In addition, phase change microcapsules are a kind of cooling functional finishing agent derived from the cold storage technology of phase change material microcapsules. When the temperature of the external environment changes, the phase change material will undergo a solid-liquid transformation. When the phase change material components undergo an endothermic reaction, they will change from solid to liquid, accompanied by the absorption of heat, thereby absorbing heat to make the fabric feel cool when touched. The use of compound microcapsules can make the fabric slowly release the cooling factor while maintaining a cool touch, and combined with the special properties of the phase change material, further improve the cooling performance.
[0061] In an optional embodiment, the slurry includes a cool finishing agent COOL and a cool finishing agent T802.
[0062] In an optional embodiment, the slurry includes: a cool finishing agent COOL 8-20 g / L and a cool finishing agent T8028-20 g / L, a hydrophobic finishing agent 20-30 wt %, a second cross-linking agent 0.1-1 g / L, an aqueous thickener 0.04-0.15% and the balance water.
[0063] In an optional embodiment, the aqueous thickener is selected from aqueous polyurethane thickeners and natural organic polymer thickeners, such as sodium alginate, cellulose, etc.;
[0064] And / or, the hydrophobic finishing agent is selected from silicone hydrophobic agents, such as polydimethylsiloxane, polysiloxane-modified waterborne polyurethane, silicone-modified polyacrylate, etc.;
[0065] And / or, the second cross-linking agent is selected from at least one of etherified hydroxymethyl melamine, ethylene oxide-based compounds, citric acid and polycarboxylic acids.
[0066] In an optional embodiment, the negative ion finishing comprises: using a negative ion foam composite material to cover the outer layer of the fabric to be finished, then pre-baking at a temperature of 60-80°C for 2-4 minutes, and then baking at a temperature of 120-140°C for 1-3 minutes to complete the outer layer finishing. In some embodiments, the compound negative ion finishing liquid foam is transferred to the outer layer of the composite fabric by a film applicator.
[0067] In an optional embodiment, the negative ion foam composite material includes 28-56 g / L of tourmaline negative ion finishing liquid, 12-24 g / L of nano inorganic metal compound negative ion finishing liquid, 2-4 g / L of foaming agent and 1-2 g / L of foam stabilizer.
[0068] Tourmaline is attached to the outer fiber. Under certain external energy, such as sunlight, wind, and friction, the energy generated by the potential difference between tourmaline crystals is enough to ionize the surrounding air. After contacting with water molecules and oxygen molecules, an ionization effect will occur to form negative ions. Inorganic metal oxide negative ion finishing agents are applied to fabrics. Inorganic metal compound negative ion finishing agents with nano-particle size can release hydroxyl negative ions existing in the original ecological conditions of primeval forests and waterfalls during the use of textiles. The compound negative ion finishing liquid not only makes the fabric release negative ions but also has anti-ultraviolet function. Negative ion fiber and cellulose fiber are blended as the outer fiber, and tourmaline is attached to the outer fiber to form an uneven structure, which can increase the absorption of light, increase the release of negative ions, help relieve fatigue, and has antibacterial and anti-ultraviolet properties. In negative ion foam composite materials, the foaming agent is anionic foaming agent (alkyl sulfates, base sulfonates, alkyl carboxylates, etc.), cationic foaming agent (salts derived from organic amines), non-ionic foaming agent (alkylphenol polyoxyethylene ether, alkyl alcohol polyoxyethylene ether, etc.) and amphoteric foaming agent (amino acid type, betaine type, imidazoline type, etc.); foam stabilizers are mainly thickening foam stabilizers (carboxymethyl cellulose, polyvinyl alcohol, etc.), ammonium stearate and hydroxyethyl cellulose (HEC), etc.
[0069] In an optional embodiment, the raw materials of the negative ion foam composite material are mixed and stirred at a shear rate of 500-2000 r / min for 3-5 min to obtain the negative ion foam composite material.
[0070] The use of foam negative ion finishing can reduce fabric damage, is suitable for a variety of fibers, and is environmentally friendly.
[0071] The present application also provides a cool anion fabric, which is prepared by the method for preparing a cool anion fabric described in any one of the above embodiments.
[0072] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0073] Example 1
[0074] High-density polyethylene fiber / nylon 6 core-skin composite fiber and modal (75:25) blended as inner fiber, bamboo charcoal fiber and modal (75:25) blended as outer fiber, inner and outer blended fibers were blended in a ratio of 1:1 to prepare spring and summer cool negative ion knitted double-sided structure fabric with a gram weight of 180 grams. Harrick basic plasma cleaning machine PDC-32G-2 was used to treat the blended fabric for 9 minutes at a maximum RF power of 18W.
[0075] The above blended fabric is subjected to cool finishing. A spraying process is used, and a 5g / L citric acid crosslinking agent solution is prepared and quantitatively sprayed (the spraying amount is 80g / m 3 ), and then dried at 140℃ for 6min. The single-sided hydrophobic finishing was carried out by screen printing process, and the hydrophobic finishing area was 40%. 40% of the compound microcapsule cooling agent, 20% of the polydimethylsiloxane hydrophobic finishing agent, 10% of the citric acid cross-linking agent (concentration of 1g / L), 10% of the sodium alginate solution (concentration of 0.8%) and 20% of the deionized water were mixed into a pulp, wherein the compound microcapsules were 50g / L of the cooling finishing agent COOL (xylitol and peppermint oil nano-microcapsules) and 50g / L of the cooling finishing agent T802 (automatic temperature-regulating microcapsules with higher alkanes as the main components) in a ratio of 1:1, and the printing pattern was designed as a geometric pattern. After the slurry was scraped at a uniform speed, the fabric was pre-dried at 110℃ for 3min, baked at 140℃ for 3min, soaped, dried and ironed to obtain the finished product.
[0076] The above blended fabrics were subjected to negative ion finishing. A single-sided foam finishing method was adopted. Initially, a foaming agent and a foam stabilizer were added to the compound negative ion finishing liquid. The foaming agent was sodium dodecyl sulfate SDS 2g / L, and the foam stabilizer was hydroxyethyl cellulose HEC 1g / L. The shear rate of the pre-set stirrer was set to 2000r / min at room temperature, and the finishing liquid was stirred and foamed for 3min to form a negative ion foam composite material. Among them, the compound negative ion finishing liquid was mixed with 45g / L of negative ion finishing agent SL-797 finishing liquid (the main component was a mixture of tourmaline powder and polyacrylamide) and 45g / L of negative ion finishing agent JYK AI-350 finishing liquid (the main component was a mixture of nano inorganic metal compounds) in a ratio of 7:3. Subsequently, the compound negative ion finishing liquid foam was transferred to the outer layer of the composite fabric by a film applicator. After pre-baking at a temperature of 80°C for 4min, it was baked at a temperature of 120°C for 3min.
[0077] The air permeability of the prepared spring and summer cool negative ion knitted fabric reaches 382mm / s and the moisture permeability reaches 10182g / (m 2 ·24h), water absorption rate reaches 122%, drip diffusion time reaches 3s, wicking height reaches 98mm, drying rate reaches 0.3 (g / h), UV transmittance (UVA, UVB are less than 5%) and UPF value reaches more than 40, antibacterial rate reaches 80%, and negative ion generation can reach 2528 / cm 3 , cool touch before washing max Can reach 0.22J / (cm 2 ·s), cool to touch after washing 5 times q max Can reach 0.21J / (cm 2 ·s).
[0078] Comparative Example 1
[0079] A preparation method of a cool negative ion fabric in spring and summer, wherein the steps are substantially the same as those in Example 1, except that the compound negative ion finishing liquid is prepared by mixing 45 g / L of a negative ion finishing agent SL-797 finishing liquid (mainly composed of a mixture of tourmaline powder and polyacrylamide) and 45 g / L of a negative ion finishing agent JYK AIT-150 finishing liquid (mainly composed of a mixture of nano inorganic metal compounds) in a ratio of 7:3.
[0080] The amount of negative ions generated by the prepared fabric before washing was only 1328 / cm 3 After washing 5 times, the amount of negative ions generated was only 928 / cm 3 , significantly decreased, the negative ion finishing agent and the hydroxyl or amine group on the fiber formed fewer chemical bonds, resulting in a decrease in the product's wash fastness and antibacterial effect.
[0081] Comparative Example 2
[0082] A method for preparing a cool anion fabric in spring and summer, wherein the steps are basically the same as those in Example 1, except that during the cool finishing process, no crosslinking agent spray finishing is used, and a screen printing process is directly performed to finish the composite microcapsules on the fabric, and the prepared fabric has a cool touch feeling q before washing. max Only 0.18J / (cm 2 ·s), cool to touch after washing 5 times q max Only 0.15J / (cm 2 ·s), poor washing resistance, this is because in the absence of a cross-linking agent, the composite microcapsules have weak adhesion to the fabric and are easy to fall off.
[0083] Comparative Example 3
[0084] A method for preparing a cool negative ion fabric in spring and summer, wherein the steps are basically the same as those in Example 1, except that a blend of high-density polyethylene fiber / nylon 6 core-sheath composite fiber and modal (25:75) is selected as an inner layer fiber, and a blend of bamboo charcoal fiber and modal (25:75) is selected as an outer layer fiber. The blended fabric prepared by the method has a cool contact feeling q max Only 0.18J / (cm 2 ·s), the amount of negative ions generated is only 1628 / cm 3 , the antibacterial and anti-ultraviolet properties decrease. This is because the proportion of functional fibers in the inner and outer layers decreases, and the cool feeling on contact and the amount of negative ions generated will also decrease.
[0085] Comparative Example 4
[0086] A method for preparing a cool anion fabric in spring and summer, wherein the steps are basically the same as those in Example 1, except that the blended fabric does not distinguish between inner and outer fibers, and directly blends high-density polyethylene fiber / nylon 6 core-sheath composite fiber and modal (75:25) blended fiber and bamboo charcoal fiber and modal (75:25) blended fiber to form a cool anion fiber. The blended fabric prepared by the method has a cool contact feeling of q max Only 0.20J / (cm 2 ·s), the amount of negative ions generated is only 2234 / cm 3 This is because without the design of the inner and outer layer structure, the layer close to the skin is not flat enough, resulting in a decrease in skin-friendliness and cooling performance. At the same time, the amount of negative ions generated by the negative ion fibers close to the outside will decrease.
[0087] Example 2
[0088] High-density polyethylene fiber / nylon 6 core-skin composite fiber and lyocell (75:25) were blended as the inner fiber, bamboo charcoal fiber and lyocell (75:25) were blended as the outer fiber, and the inner and outer blended fibers were blended in a ratio of 1:1 to prepare a spring and summer cool negative ion knitted double-sided structure fabric with a gram weight of 180 grams. Harrick basic plasma cleaning machine PDC-32G-2 was used to treat the blended fabric for 9 minutes at a maximum radio frequency power of 18W.
[0089] The above blended fabric is subjected to cool finishing. A spraying process is used, and a 5g / L citric acid crosslinking agent solution is prepared and quantitatively sprayed (the spraying amount is 80g / m 3 ), and then dried at 140℃ for 6min. 70% of the compound microcapsule cooling agent, 20% of the nonionic adhesive and 10% of the nonionic thickener were mixed into a pulp. Among them, the compound microcapsules were compounded in a ratio of 1:1 using 50g / L of the cooling finishing agent COOL (xylitol and peppermint oil nano-microcapsules) and 50g / L of the cooling finishing agent T802 (automatic thermostatic microcapsules with higher alkanes as the main component). The single-sided hydrophobic finishing was performed using the screen printing process, and the hydrophobic finishing area was 40%. 40% of the compound microcapsule cooling agent, 20% of the polydimethylsiloxane hydrophobic finishing agent, 10% of the citric acid crosslinking agent (concentration of 1g / L), 10% of the sodium alginate solution (concentration of 0.8%) and 20% of the deionized water were mixed into a pulp. The printing pattern was designed as a geometric pattern. After the pulp was scraped at a uniform speed, the fabric was pre-dried at 110℃ for 3min, baked at 140℃ for 3min, and soaped, dried and ironed to obtain the finished product.
[0090] The above blended fabrics were subjected to negative ion finishing. Using a single-sided foam finishing method, initially, a compound negative ion finishing liquid, 2g / L of a foaming agent, sodium dodecyl sulfate SDS, and 1g / L of a foam stabilizer, hydroxyethyl cellulose HEC, were added to a certain volume of water. The shear rate of the preset stirrer was set to 2000r / min at room temperature, and the finishing liquid was stirred and foamed for 3min to form a negative ion foam composite material. Among them, the compound negative ion finishing liquid was mixed with 45g / L of a negative ion finishing agent SL-797 finishing liquid (the main component of which was a mixture of tourmaline powder and polyacrylamide) and 45g / L of a negative ion finishing agent JYK AI-350 finishing liquid (the main component of which was a mixture of nano-inorganic metal compounds) in a ratio of 7:3. Subsequently, the compound negative ion finishing liquid foam was transferred to the outer layer of the composite fabric by a film applicator. After pre-baking at a temperature of 80°C for 4min, it was baked at a temperature of 120°C for 3min.
[0091] The air permeability of the prepared spring and summer cool negative ion knitted fabric reaches 388mm / s and the moisture permeability reaches 11456g / (m 2 24h), UV transmittance (UVA and UVB are less than 5%) and UPF value reach more than 50, water absorption rate reaches 113%, drip diffusion time reaches 3s, wicking height reaches 97mm, drying rate reaches 0.3 (g / h), Escherichia coli inhibition rate reaches 80%, and negative ion generation can reach 2578 / cm 3 , cool touch before washing max Can reach 0.21J / (cm 2 ·s), cool to touch after washing 5 times q max Can reach 0.20J / (cm 2 ·s).
[0092] Example 3
[0093] High-density polyethylene fiber / nylon 6 core-skin composite fiber and viscose fiber (75:25) were blended as the inner fiber, bamboo charcoal fiber and viscose fiber (75:25) were blended as the outer fiber, and the inner and outer blended fibers were blended in a ratio of 1:1 to prepare a spring and summer cool negative ion knitted double-sided structural fabric with a gram weight of 180 grams. Harrick basic plasma cleaning machine PDC-32G-2 was used to treat the blended fabric for 9 minutes at a maximum radio frequency power of 18W.
[0094] The above blended fabric is subjected to cool finishing. A spraying process is used, and a 5g / L citric acid crosslinking agent solution is prepared and quantitatively sprayed (the spraying amount is 80g / m 3), and then dried at 140℃ for 6min. 70% of the compound microcapsule cooling agent, 20% of the nonionic adhesive and 10% of the nonionic thickener were mixed into a pulp. Among them, the compound microcapsules were compounded in a ratio of 1:1 using 50g / L of the cooling finishing agent COOL (xylitol and peppermint oil nano-microcapsules) and 50g / L of the cooling finishing agent T802 (automatic thermostatic microcapsules with higher alkanes as the main component). The single-sided hydrophobic finishing was performed using the screen printing process, and the hydrophobic finishing area was 40%. 40% of the compound microcapsule cooling agent, 20% of the polydimethylsiloxane hydrophobic finishing agent, 10% of the citric acid crosslinking agent (concentration of 1g / L), 10% of the sodium alginate solution (concentration of 0.8%) and 20% of the deionized water were mixed into a pulp. The printing pattern was designed as a geometric pattern. After the pulp was scraped at a uniform speed, the fabric was pre-dried at 110℃ for 3min, baked at 140℃ for 3min, and soaped, dried and ironed to obtain the finished product.
[0095] The above blended fabrics were subjected to negative ion finishing. Using a single-sided foam finishing method, initially, a compound negative ion finishing liquid, 2g / L of a foaming agent, sodium dodecyl sulfate SDS, and 1g / L of a foam stabilizer, hydroxyethyl cellulose HEC, were added to a certain volume of water. The shear rate of the preset stirrer was set to 2000r / min at room temperature, and the finishing liquid was stirred and foamed for 3min to form a negative ion foam composite material. Among them, the compound negative ion finishing liquid was mixed with 45g / L of a negative ion finishing agent SL-797 finishing liquid (the main component of which was a mixture of tourmaline powder and polyacrylamide) and 45g / L of a negative ion finishing agent JYK AI-350 finishing liquid (the main component of which was a mixture of nano-inorganic metal compounds) in a ratio of 7:3. Subsequently, the compound negative ion finishing liquid foam was transferred to the outer layer of the composite fabric by a film applicator. After pre-baking at a temperature of 80°C for 4min, it was baked at a temperature of 120°C for 3min.
[0096] The air permeability of the prepared spring and summer cool negative ion knitted fabric reaches 367mm / s and the moisture permeability reaches 13462g / (m 2 24h), UV transmittance (UVA and UVB are less than 5%) and UPF value reach more than 50, water absorption rate reaches 134%, drip diffusion time reaches 3s, wicking height reaches 96mm, drying rate reaches 0.3 (g / h), Escherichia coli inhibition rate reaches 80%, and negative ion generation can reach 2365 / cm 3 , cool touch before washing max Can reach 0.22J / (cm 2 ·s), cool to touch after washing 5 times q max Can reach 0.21J / (cm 2 ·s).
[0097] Example 4
[0098] The blend of jade fiber and modal (75:25) was selected as the inner fiber, and the blend of bamboo charcoal fiber and modal (75:25) was selected as the outer fiber. The inner and outer blended fibers were blended in a ratio of 1:1 to prepare a spring and summer cool negative ion knitted double-sided structure fabric with a gram weight of 180 grams. The Harrick basic plasma cleaning machine PDC-32G-2 was used to treat the blended fabric for 9 minutes at a maximum radio frequency power of 18W.
[0099] The above blended fabric is subjected to cool finishing. A spraying process is used, and a 5g / L citric acid crosslinking agent solution is prepared and quantitatively sprayed (the spraying amount is 80g / m 3 ), and then dried at 140℃ for 6min. 70% of the compound microcapsule cooling agent, 20% of the nonionic adhesive and 10% of the nonionic thickener were mixed into a pulp. Among them, the compound microcapsules were compounded in a ratio of 1:1 using 50g / L of the cooling finishing agent COOL (xylitol and peppermint oil nano-microcapsules) and 50g / L of the cooling finishing agent T802 (automatic thermostatic microcapsules with higher alkanes as the main component). The single-sided hydrophobic finishing was performed using the screen printing process, and the hydrophobic finishing area was 40%. 40% of the compound microcapsule cooling agent, 20% of the polydimethylsiloxane hydrophobic finishing agent, 10% of the citric acid crosslinking agent (concentration of 1g / L), 10% of the sodium alginate solution (concentration of 0.8%) and 20% of the deionized water were mixed into a pulp. The printing pattern was designed as a geometric pattern. After the pulp was scraped at a uniform speed, the fabric was pre-dried at 110℃ for 3min, baked at 140℃ for 3min, and soaped, dried and ironed to obtain the finished product.
[0100] The above blended fabrics were subjected to negative ion finishing. Using a single-sided foam finishing method, initially, a compound negative ion finishing liquid, 2g / L of a foaming agent, sodium dodecyl sulfate SDS, and 1g / L of a foam stabilizer, hydroxyethyl cellulose HEC, were added to a certain volume of water. The shear rate of the preset stirrer was set to 2000r / min at room temperature, and the finishing liquid was stirred and foamed for 3min to form a negative ion foam composite material. Among them, the compound negative ion finishing liquid was mixed with 45g / L of a negative ion finishing agent SL-797 finishing liquid (the main component of which was a mixture of tourmaline powder and polyacrylamide) and 45g / L of a negative ion finishing agent JYK AI-350 finishing liquid (the main component of which was a mixture of nano-inorganic metal compounds) in a ratio of 7:3. Subsequently, the compound negative ion finishing liquid foam was transferred to the outer layer of the composite fabric by a film applicator. After pre-baking at a temperature of 80°C for 4min, it was baked at a temperature of 120°C for 3min.
[0101] The air permeability of the prepared spring and summer cool negative ion knitted fabric reaches 378mm / s and the moisture permeability reaches 13465g / (m 224h), UV transmittance (UVA and UVB are less than 5%) and UPF value reach more than 50, water absorption rate reaches 113%, drip diffusion time reaches 3s, wicking height reaches 108mm, drying rate reaches 0.3 (g / h), Escherichia coli inhibition rate reaches 80%, and negative ion generation can reach 2420 / cm 3 , cool touch before washing max Can reach 0.21J / (cm 2 ·s), cool to touch after washing 5 times q max Can reach 0.20J / (cm 2 ·s).
[0102] In the above tests, the air permeability test refers to GB / T 5453-1997 "Determination of air permeability of textile fabrics", the washing method test refers to GB / T 8629-2017 "Household washing and drying procedures for testing textiles", the test method of water vapor permeability refers to GB / T 12704.1-2009 "Test method for water vapor permeability of textile fabrics Part 1: Moisture absorption method", the anti-ultraviolet performance refers to GB / T 18830-2009 "Evaluation of UV protection of textiles", the test method of antibacterial rate refers to GB / T 20944.3-2008 "Evaluation of antibacterial property of textiles Part 3: Oscillation method", the test methods of water absorption rate, drip diffusion time, wicking height and drying rate all refer to GB / T 21655.1-2023 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method", and the test method of negative ion generation refers to GB / T 30128-2013 "Testing and Evaluation of Negative Ion Generation of Textiles", and the contact cooling performance refers to GB / T 35263-2017 "Testing and Evaluation of the Instantaneous Cooling Performance of Textiles".
[0103] Table 1
[0104]
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cool negative ion fabric, characterized in that: include: The negative ion fiber is blended and interwoven with the cellulose fiber to obtain an inner layer fabric, the cool feeling fiber is blended and interwoven with the cellulose fiber to obtain an outer layer fabric, and the inner layer fabric and the outer layer fabric are interwoven and interwoven to obtain a fabric to be finished; The inner layer of the fabric to be finished is sequentially subjected to plasma treatment and cooling microcapsule finishing; the outer layer of the fabric to be finished is sequentially subjected to plasma treatment and negative ion finishing to obtain the cooling negative ion fabric.
2. The method for preparing the cool negative ion fabric according to claim 1, characterized in that: Meet at least one of the following characteristics: a. The mass fraction of negative ion fibers in the inner layer fabric is 70%-90%; b. The mass fraction of cool fibers in the outer fabric is 70%-90%; c. The mass fraction of the inner layer of the fabric to be finished is 40%-60%; d. Cellulose fiber is selected from at least one of cotton fiber, modal, lyocell and viscose fiber; e. Cooling fibers are selected from at least one of nylon, polyethylene nylon fiber and jade fiber; f. Anion fiber is selected from at least one of bamboo charcoal fiber, germanium alloy fiber and rice husk carbon fiber; g. The weave structure of the fabric to be finished is selected from one of double-sided fabric, pique weave and rib weave.
3. The method for preparing the cool negative ion fabric according to claim 1, characterized in that: The plasma treatment step includes: using a plasma cleaning machine to perform plasma treatment on the inner layer and the outer layer of the fabric to be finished, with a maximum radio frequency power of 17-19W and a treatment time of 6-10min; And / or, the cooling microcapsule finishing comprises: firstly finishing the inner layer of the fabric to be finished with a first cross-linking agent, and then finishing the inner layer of the fabric to be finished with a composite microcapsule.
4. The method for preparing the cool negative ion fabric according to claim 3, characterized in that: The first cross-linking agent is selected from at least one of an organosilicon cross-linking agent, a polycarboxylic acid cross-linking agent and a polyacrylate cross-linking agent; And / or, using the first crosslinking agent to finish the inner layer of the fabric to be finished after the plasma treatment includes: spraying 5-10g / L of the first crosslinking agent solution to the inner layer of the fabric to be finished, and then drying at 110-130°C for 5-7min, wherein the spraying amount is 70g / m 3 -120g / m 3 .
5. The method for preparing the cool negative ion fabric according to claim 3, characterized in that: The method of using the composite microcapsules to finish the inner layer of the fabric to be finished comprises: firstly using the screen printing process to perform single-sided hydrophobic finishing, with the hydrophobic finishing area being 30-50%, coating the slurry containing the composite microcapsules on the inner surface of the fabric to be finished by scraping, pre-baking the fabric at 100-120°C for 1-3min, then baking at 130-160°C for 1-3min, and then soaping, drying and ironing to complete the inner layer finishing.
6. The method for preparing the cool negative ion fabric according to claim 5, characterized in that: The slurry includes a cool finishing agent COOL and a cool finishing agent T802.
7. The method for preparing the cool negative ion fabric according to claim 5, characterized in that: The slurry comprises: 8-20 g / L of a cool finishing agent COOL and 8-20 g / L of a cool finishing agent T802, 20-30 wt % of a hydrophobic finishing agent, 0.1-1 g / L of a second cross-linking agent, 0.04-0.15% of a water-based thickener and the balance of water.
8. The method for preparing the cool negative ion fabric according to claim 7, characterized in that: The water-based thickener is selected from water-based polyurethane thickeners and natural organic polymer thickeners; And / or, the hydrophobic finishing agent is selected from silicone hydrophobic agents; And / or, the second cross-linking agent is selected from at least one of etherified hydroxymethyl melamine, ethylene oxide-based compounds, citric acid and polycarboxylic acids.
9. The method for preparing the cool negative ion fabric according to claim 1, characterized in that: The negative ion finishing comprises: using a negative ion foam composite material to cover the outer layer of the fabric to be finished, then pre-baking at a temperature of 60-80°C for 2-4 minutes, and baking at a temperature of 120-140°C for 1-3 minutes to complete the outer layer finishing; Preferably, the negative ion foam composite material comprises 28-56 g / L of tourmaline negative ion finishing liquid, 12-24 g / L of nano inorganic metal compound negative ion finishing liquid, 2-4 g / L of foaming agent and 1-2 g / L of foam stabilizer; Preferably, the raw materials of the negative ion foam composite material are mixed and stirred at a shear rate of 500-2000 r / min for 3-5 min to obtain the negative ion foam composite material.
10. A cool negative ion fabric, characterized in that: The cool anion fabric is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Anion health care finishing technology of all cotton jacquard fabric
CN104746266A
Preparation method of fabric capable of enhancing cool feeling
CN112501915A
Negative-ion cool double-layer knitted fabric
CN202482567U
Cool sense knitted fabric of anion
CN205133910U
Cooling lightweight fabrics and cooling lightweight clothing
JP3239687U
Cited By
Ice-feeling bio-based lyocell fabric as well as preparation method and application thereof
CN121572703A
Ice-sensing bio-based lyocell fabric and preparation method and application thereof
CN121572703B